ATAVILLOS CONTEXTS FUNERAL IN PURUNMARCA, VICHAYCOCHA – HUARAL - van Dalen Luna, Pieter (2015)
The upper basin of the river Chancay-Huaral, Atavillos occupied by the pre-Hispanic culture in late periods, is an almost unknown territory, despite the existence of numerous settlements of great importance as Rupac, Chiprac, Añay, Cachirmarca, among others. San Miguel de Vichaycocha farming community is the highest altitude in the basin, bordering the province of Huayllay via Antajirca Range area where interactions between Atavillos and other peoples as Chinchaycocha, Yaros, etc. were performed In the area of this community there are numerous settlements Atavillos, the most important of Purunmarca, where research with excavations of the 2014 season helped identify areas of multiple activity, as well as the characteristics of the funerary contexts.